Barrier Functions‐Based Adaptive Integral Terminal Sliding Mode Control for Output‐Constrained Uncertain Nonlinear Systems - Jiang, Daogen; Lv, Longjin; Song, Sunhao; Zhu, Xiaodong (International journal of adaptive control and signal processing, 2025)
Herein, a new barrier function (BF)‐based adaptive integral terminal sliding mode control (ABF‐ITSMC) with output constraints methodology is proposed for high‐order nonlinear systems (HONSs) exposed to unknown lumped disturbance. The proposed algorithms utilize the backstepping control (BSC) technique for management of high‐order mismatched uncertainties by incorporating the dynamic surface control (DSC) via first order low pass filter (FOLPF) to eliminate “complexity explosion.” To deal with the output constraints requirement, a barrier Lyapunov function is introduced for the design of the virtual control law. Besides, an integrate sliding manifold surface is designed to obtain the finite time convergent and singularity free features to enhance the robustness. Additionally, an adaption control gain law is devised by BF to precisely estimate the real‐time lumped disturbance without the requirement of any boundary information. Lyapunov stability theory is employed for proving that the uniformly and eventually bounded tracking deviation of the overall system. Lastly, simulations with two cases are conducted to validate the devised method with respect to the strength and effectiveness by comparing the derived outcomes of the method with that of the existing method.